The use of Radio Frequency Identification to track samples in bio-repositories - GRIMSON, JANE BARCLAY (IEEE, 2008)
Bio-repositories are resources for storing biological samples and data to support the discovery of biomarkers, therapeutic targets, and the underlying causes of diseases. The success of this knowledge discovery process depends critically on the quality of samples and their associated data. Biological samples are expensive to collect and store. The samples and their associated data pass through a number of processes, generally in multiple locations, from data collection from the participant, to clinical laboratory analyses, to processing in the research laboratory (proteomics, metablomics, etc.) and ultimately to knowledge discovery. The samples are moved in and out of freezers at several different points in this workflow. The potential for errors in sample identification and linking the corresponding data to its sample is therefore very high. This paper describes a novel method based on Radio Frequency Identification (RFID) technology to support secure and reliable tracking of both samples and data which minimises the potential for error. The samples are labelled with RFID tags, which allow location-independent recording and updating of sample data as they move along the workflow. The system is linked to a web-based database, which provides the ability to identify and locate individual or group of samples rapidly.
IEEE International Conference on Information Technology: Ist: Gdansk, Poland, 2008
PUBLISHED
Keywords: Web-based database; bio-repositories; biological samples; biomarkers; knowledge discovery; radio frequency identification; reliable tracking; therapeutic targets